Experimental analysis of density and compressive strain of porous metal with the use of Taylor test (Archives of Mechanics - Test, 2014)
The article presents a new experimental method of analysis of density and longitudinal engineering compressive strain (LECS) in porous ductile rod, plastically deformed with a Taylor direct impact experiment (Taylor DIE). Two essential singularities in the distribution of the LECS are revealed, namely: maximum of the LECS εr max occurs near the rod striking end (Fig. 2), and at high impact velocities (U > 100 m/s) εr max decreases along with an increase of the rod initial porosity, this behaviour is inverse to that under static loading. The dynamical density – LECS curves for porous copper are also presented in the paper. According to the authors’ best knowledge, these singularities have not been published in available literature so far.